FAILURE ANALYSIS OF PRESTRESSED CONCRETE STEEL BAR DURING THE INITIAL DRAWING PROCESS - Toni Agung Priambodo; Apriardi Ihlas (Jurnal Teknologi Bahan dan Barang Teknik, 2021)
Reinforced concrete is a common structural material used in the modern era. High tension steel provides strength to the concrete structure to reduce internal tensile forces and eliminate cracking. Failure of reinforcing steel causes the reinforced concrete to not have optimal strength and has the potential to cause failure in the main structure. The present paper describes the investigation of the failure case in the prestressed concrete bar (PC bar) during the manufacture of prestressed or pre-tensioned concrete. The failure occurred in the head section area during the initial drawing process. The chemical composition and tensile test showed the raw material complied to the manufacturer's specification. The fractography and microscopic examination of the failure area showed the characteristics of brittle fracture. Stress concentration in the head section and the tempering process of PC bar after quenching process at an inappropriate temperature caused temper embrittlement to be the cause of failure during the initial drawing process.